The effect of hypoxia on facial shape variation and disease phenotypes in chicken embryos - Francis Smith; Diane Hu; Nathan M. Young; Alexis J. Lainoff; Heather A. Jamniczky; Emin Maltepe; Benedikt Hallgrimsson; Ralph S. Marcucio (The Company of Biologists, 2013)
SUMMARY Craniofacial anomalies can arise from both genetic and environmental factors, including prenatal hypoxia. Recent clinical evidence correlates hypoxia to craniofacial malformations. However, the mechanisms by which hypoxia mediates these defects are not yet understood. We examined the cellular mechanisms underlying malformations induced by hypoxia using a chicken (Gallus gallus) embryo model. Eggs were incubated in either hypoxic (7, 9, 11, 13, 15, 17 or 19% O2) or normoxic (21% O2) conditions. Embryos were photographed for morphological analysis at days 3-6. For analysis of skeletal development, 13-day embryos were cleared and stained with alcian blue and alizarin red for cartilage and bone, respectively. Quantitative analysis of facial shape variation was performed on images of embryos via geometric morphometrics. Early-stage embryos (day 2) were analyzed for apoptosis via whole-mount and section TUNEL staining and immunostaining for cleaved caspase-3, whereas later-stage embryos (days 4-6) were sectioned in paraffin for analysis of cell proliferation (BrdU), apoptosis (TUNEL) and metabolic stress (phospho-AMPK). Results demonstrate that survival is reduced in a dose-dependent manner. Hypoxic embryos displayed a spectrum of craniofacial anomalies, from mild asymmetry and eye defects to more severe frontonasal and cephalic anomalies. Skull bone development was delayed in hypoxic embryos, with some skeletal defects observed. Morphometric analysis showed facial shape variation relative to centroid size and age in hypoxic groups. Hypoxia disrupted cell proliferation and, in early-stage embryos, caused apoptosis of neural crest progenitor cells. Hypoxic embryos also displayed an increased metabolic stress response. These results indicate that hypoxia during early embryonic craniofacial development might induce cellular oxidative stress, leading to apoptosis of the neural crest progenitor cells that are crucial to normal craniofacial morphogenesis.